Factor Analysis of Knowledge Attitude and Characteristics of Nurses Towards Pain Management - Saodah Hanim; Siti Saidah Nasution; Tasrif Hamdi (Indonesian Journal of Global Health Research, 2024)
Pain is an experience of subjective and physiological condition. Accurate pain assessment is essential and effective for the successful implementation of pain management. The inability of nurses to assess pain and poor communication between patients and nurses leads to ineffective pain management. In addition, an adequate level of knowledge and a positive attitude in caring for patients is an important component in the delivery of pain management. Objective: The purpose of this study was to analyze the factor of knowledge and attitude of nurses towards pain management at Haji Adam Malik Hospital Medan. Method: The type of research used in this study was quantitative with a survey method research design. Respondents in the study amounted to 84 nurses in the RB6. RA3, RA4 dan RA5. Bivariate Data Analysis with Chi-Square. Results: The result chi-square test analysis obtained a p-value for the variable of age (0,472). Education (0,790). Experience (),376), knowledge (0,099), and attitude  (0,000). Conclusions: Attitude is the nurse's readiness or willingness to act in the assessment and reassessment of pain, managing pain, and evaluating it. Good nursing attitudes are needed to improve the implementation of pain management at the H. Adam Malik Central General Hospital, Medan.